2018
DOI: 10.1080/21681805.2018.1428683
|View full text |Cite
|
Sign up to set email alerts
|

The narrow vesicourethral angle measured on postoperative cystography can predict urinary incontinence after robot-assisted laparoscopic radical prostatectomy

Abstract: A narrow vesical angle measured on cystography is a useful predictor of postoperative urinary incontinence after RALP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
5
14
0
Order By: Relevance
“…The VBDD was not significantly different between the two groups preoperatively and postoperatively, suggesting that urethral hypermobility during voiding is not involved in PPI. Some studies have advocated that a smaller PUVA after RP contributes to early continence recovery 19,25 . In our study, the PUVA of the continence group was significantly smaller than that of the incontinence group during the resting and voiding phases only after surgery, thus supporting the results of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…The VBDD was not significantly different between the two groups preoperatively and postoperatively, suggesting that urethral hypermobility during voiding is not involved in PPI. Some studies have advocated that a smaller PUVA after RP contributes to early continence recovery 19,25 . In our study, the PUVA of the continence group was significantly smaller than that of the incontinence group during the resting and voiding phases only after surgery, thus supporting the results of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Postoperative cystography is a useful tool for predicting post-prostatectomy incontinence. A higher vesico-urethral anastomosis location is associated with a higher rate of early recovery of UC, and a wider bladder neck angle is associated with a high rate of early recovery of UC (12)(13)(14)(15)(16). Our data also demonstrated that early recovery of UC was observed in patients with wider bladder neck angle, however the postoperative location of bladder neck did not show any significant association with early recover of UC after NNS-LRP in multivariate analysis.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have reported several factors associated with postoperative UI: i) demographic factors, including age, prostate volume, prostatic apical shape, membranous urethral length and preoperative lower urinary tract symptoms (LUTS) (3)(4)(5)(6)(7)(8), ii) surgical technique-related factors, including posterior and anterior wall reconstruction, nerve sparing procedure, and bladder neck preservation, which are potentially related to the early recovery of postoperative urinary continence (UC) (9)(10)(11). In addition to preoperative and intraoperative factors, postoperative findings, such as cystography suggested to be a reliable tool for predicting postoperative UI (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…This method was simple, but it did not offer an immediate predictor of continence recovery following catheter removal. Several researches [3][4][5] reported their static cystographic findings after prostatectomy. As they have been reported, many static cystographic findings could estimate the postoperative urinary continence.…”
Section: Discussionmentioning
confidence: 99%
“…These injuries often delay patients' recovery from postoperative incontinence [1]. Therefore, many researchers reported the various static imaging parameters to represent the postoperative status of periurethral muscles [3][4][5]. However, we believed that this status should be evaluated with dynamic diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%